Review on Project Management Tools - Tarika, Bindia (International Journal of Computer Sciences and Engineering, 2020)
Project management involves with effective plans and systematically organization of work. It includes defining the project objectives, making schedules and assigning tasks, in order to accomplish a successful goal. There are many tools that make project management more effective and efficient. The development of software for an improved business process, the construction of a building or bridge, the relief effort after a natural disaster, the expansion of sales into a new geographic market — all are projects. Project management, is the application of knowledge, skills, tools, and techniques to project activities to meet the project requirements.